The integration of information and communication technology into rural schools of South Africa :a case study of schools in Malamulele - Amedzo, Ephraim Kofi (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2007.